PENGARUH PENGUASAAN MATERI TURUNAN TERHADAP HASIL BELAJAR INTEGRAL : (The Influence Of Mastery Of Decreated Materials On Integral Learning Outcomes) - Malmia, Wa; Amir, Nur Fadhilah (Uniqbu Journal of Exact Sciences, 2021)
This study aims to determine the effect of mastery of derived material on integral learning outcomes in class XII IMIA1 SMA Negeri 2 Buru. This type of research is ex-post-facto research. The sample in this study were students of class XII IMIA1 SMA Negeri 2 Buru totaling 30 students. The instruments used in this study were in the form of derivative material test questions and integral material test scores. The data obtained were then analyzed using the SPSS 24 for windows program. The results of this study indicate that there is a significant influence on the mastery of derived material on the learning outcomes of integral material for XII IMIA1 grade students of SMA Negeri 2 Buru. This can be seen from the form of a simple linear regression equation which is characterized by the results of the t test, namely thit> ttab both at the real level ???? = 0.05. While the magnitude of the effect of mastery of derived material on learning outcomes of integral material for students of class XII IMIA1 SMA Negeri 2 Buru was 0.819 or 81.9%.